Effect of Different Additives on Viscosity and Flow Bheaviour of Fly Ash Slurries - Rajaji, R.; Sekar, K.G. (Asian Journal of Chemistry, 2010)
The quantity of fly ash produced in such power stations is quite enormous. The ash produced in such power stations is at present being disposed to mid sea if the power station is situated near the sea. Otherwise it is disposed in some waste lands. The ash produced in power stations is being mostly transported in the form of water slurry by pumping. Enormous quantity of water is being used for such transportation. From the economical point of view, it is worthwhile to explore the possibilities of reducing this enormous quantity of water being used for slurry making. This is possible only if the solid content of ash-slurry is increased thereby reducing the quantity of water used and at the same time the slurry becomes easily pumpable using slurry pumps. Loading higher solids in ash water slurries becomes possible only if the viscosity of the slurry is reduced by adding surface active agents. An attempt has been made in this study to assess the effect of organic polymers which are surfactants in reducing·the viscosity of the ash water slurries. It is proposoo to study the combined effect of mineral matter in ash, and different types of organic polymeric substanc:s on the viscosities if ash-water slurries. The results obtained and discussed herein suggest that the organic polymeric substances as additives reduce the viscosity of the ash-water slurries with better reliability.